A new record of Chironomus (Chironomus) acidophilus Keyl (Diptera, Chironomidae) from the Uzon volcanic caldera (Kronotsky Reserve, Kamchatka Peninsula, Russia), its karyotype, ecology and biology - Orel, Oksana V.; Lobkova, Ludmila E.; Zhirov, Sergey V.; Petrova, Ninel A. (Zootaxa, 2015)
Morphology, cytology, ecology and biology of Holarctic Chironomus (Chironomus) acidophilus Keyl, 1960 (Diptera, Chironomidae) was examined from material collected in the geothermal Vosmerka Lake (pH=2.0–2.5). An illustrated redescription of C. acidophilus is given on the basis of adult males reared from field-collected pupae, and of simultaneously collected larvae. Additional larvae belonging to the pseudothummi-complex were identified as C. acidophilus on the basis of their karyotype. The karyotype of C. acidophilus (2n=8) and detailed mapping of the 4 chromosome arms A, E, D and F are provided. The population of C. acidophilus from Kamchatka was found to be karyologically monomorphic. Information on distribution and ecology of C. acidophilus from Vosmerka Lake (total mineralization 1583.5 mg/l) is also given. Chironomus acidophilus is the only species of aquatic insects recorded in this lake. Lack of competition and a richness of food resources contribute to the high abundance (35161 ind./m2) and biomass (11.342 g/m2) of the larvae of C. acidophilus in Vosmerka Lake.